Nonverbal Idiomatic Expressions and Metaphorical Behaviour in Pixar’s Animated Short Film “For the Birds” - Putri Fatimah Azzahra; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines how Pixar’s animated short film For the Birds employs metaphorical behaviour and nonverbal idioms. Despite lacking spoken speech, the movie uses human emotions, physical gestures, and symbolic sequences to convey a story full of humour and social commentary. In the film, many little birds make fun of a bigger, clumsier-looking bird, only to encounter unexpected repercussions. This story, which is both quiet and expressive, provides a rare chance to examine idiomatic meanings that are expressed nonverbally. The study uses a qualitative descriptive approach to find and analyse several scenes that metaphorically illustrate well-known sayings like “don’t judge a book by its cover,” “patience is a virtue,” and “what goes around comes around.” The results demonstrate how action, gesture, and facial expression may all serve as visual languages that represent virtues like poetic justice, humility, and tolerance. These visual idioms improve the narrative by enabling viewers to deduce intricate meanings without using spoken words. Finally, by demonstrating how idioms can transcend language through metaphorical representation in multimodal texts, this study highlights the potency of visual narrative and advances the discipline of visual pragmatics